Full-time and Integral Education Policies Considering the Public Policy Cycle Analysis - Cláudia da Mota Darós Parente (Universidade Federal do Rio Grande do Sul, 2018)
This article aims to systematize some elements for the analysis of full-time and integral education policies considering the public policy cycle. The public policy cycle is composed of the following phases: agenda, formulation, implementation and evaluation. Through a theoretical essay, based on the bibliography of the public policy area and the theoretical and empirical accumulation about the subject, the present study shows how full-time and integral education policies are currently on the Brazilian political-educational agenda and how they have been formulated, implemented and evaluated. It points out the relevance of constructing analytical tools and methodologies that better capture the needs of the area.